Influence of excipients and processing conditions on the development of agglomerates of racecadotril by crystallo‑co‑agglomeration - Garala, Kevin; Patel, Jaydeep; Patel, Anjali; Raval, Mihir; Dharamsi, Abhay (International Journal of Pharmaceutical Investigation)
Purpose: The purpose of the present investigation was to improve the flow and mechanical properties of racecadotril by a crystallo‑co‑agglomeration (CCA) technique. Direct tableting is a requirement of pharmaceutical industries. Poor mechanical properties of crystalline drug particles require wet granulation which is uneconomical, laborious, and tedious. Materials and Methods: The objective of this work was to study the influence of various polymers/excipients and processing conditions on the formation of directly compressible agglomerates of the water‑insoluble drug, racecadotril, an antidiarrheal agent. The agglomerates of racecadotril were prepared using dichloromethane (DCM)—water as the crystallization system. DCM acted as a good solvent for racecadotril as well as a bridging liquid for the agglomeration of the crystallized drug and water as the nonsolvent. The prepared agglomerates were tested for micromeritic and mechanical properties. Results: The process yielded ~90 to 96% wt/ wt spherical agglomerates containing racecadotril with the diameter between 299 and 521 μ. A higher rotational speed of crystallization system reduces the size of the agglomerates and disturbs the sphericity. Spherical agglomerates were generated with a uniform dispersion of the crystallized drug. CCA showed excellent flowability and crushing strength. Conclusion: Excipients and processing conditions can play a key role in preparing spherical agglomerates of racecadotril by CCA, an excellent alternative to the wet granulation process to prepare intermediates for direct compression.
Keywords: Crystallo‑co‑agglomeration; crushing strength; flowability; racecadotril